Linking key trophic chemical indicators to spatio-temporal variabilities of fish traits and functional diversity along the Nakdong River - Namsrai Jargal; Ji Yoon Kim; Kwang-Guk An (Ecological Informatics)
Water quality deterioration remains a significant threat to freshwater ecosystems. Analysis of community structures in response to water quality is fundamental to address this issue. This study investigated spatial and seasonal fluctuations in physical and chemical parameters and their correlations with algal biomass and fish community dynamics in the Nakdong River. Imbalances in nutrient ratios, particularly elevated concentrations of phosphorus, were important drivers of increased algal biomass, measured via levels of sestonic chlorophyll-a (CHL-a). This finding suggests that phosphorus control is key to mitigating eutrophication risk. We also found that increased levels of CHL-a and organic matter were negatively associated with functional diversity, endemic species richness, and native species abundance. RLQ and fourth-corner analysis revealed significant patterns in trait-based community structure related to chemical parameters. High electric conductivity and levels of ammonium nitrogen, mainly from point-source pollution, altered the composition of the fish community, favoring invasive alien species (IAS) over native species. Spawning habitat generalists showed positive correlations with ionic content and inorganic nitrogen, primarily driven by the abundance of the large-mouth bass Micropterus salmoides. Conversely, the riffle-associated habitat guild and native species were negatively correlated with organic matter indicators. Overall, our study elucidates the multifaceted links between fish communities and water quality parameters according to functional diversity and a trait-based model based on ecological guilds and regional species status. The results underscore the potential impacts of stream water chemistry and trophic state changes on fish assemblage structures in the temperate river, providing insights for conservation actions.